2015
DOI: 10.1126/science.aab2413
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally low daily energy expenditure in the bamboo-eating giant panda

Abstract: The carnivoran giant panda has a specialized bamboo diet, to which its alimentary tract is poorly adapted. Measurements of daily energy expenditure across five captive and three wild pandas averaged 5.2 megajoules (MJ)/day, only 37.7% of the predicted value (13.8 MJ/day). For the wild pandas, the mean was 6.2 MJ/day, or 45% of the mammalian expectation. Pandas achieve this exceptionally low expenditure in part by reduced sizes of several vital organs and low physical activity. In addition, circulating levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
130
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 37 publications
3
130
3
2
Order By: Relevance
“…The shaded area from T2 to T3 was defined as the time during which F. robusta shoots were available for giant panda foraging Fig. 9 Elevational movement patterns of GPS-collared giant pandas across the year (a) and during the F. robusta bamboo shooting season (April-June) (b) proportion available energy in shoots may be the major impetus for migrational movements of giant pandas in this season, which also may account for the extensive energy intake strategy to procure them (Nie et al 2015;Li et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shaded area from T2 to T3 was defined as the time during which F. robusta shoots were available for giant panda foraging Fig. 9 Elevational movement patterns of GPS-collared giant pandas across the year (a) and during the F. robusta bamboo shooting season (April-June) (b) proportion available energy in shoots may be the major impetus for migrational movements of giant pandas in this season, which also may account for the extensive energy intake strategy to procure them (Nie et al 2015;Li et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated 1864 remaining giant pandas (State Forestry Administration of the People's Republic of China 2015) are facing many humaninduced threats including road construction, timber harvesting, and livestock grazing (Hull et al 2014;Hong et al 2015Hong et al , 2016Liu 2015;Zhang et al 2017a). Although pandas have a simple digestive tract with no enzymes to digest the cellulose that is found in fibrous bamboo culms (Hu et al 2010;Li et al 2010;Wei et al 2012;Nie et al 2015), they do have adaptations that allow them to subsist on a bamboo diet such as enlarged molars and specialized gut microbes to aid in cellulose digestion (Zhu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In ancient days giant pandas were carnivorous; however, they began to eat bamboo, a food for which their alimentary tract is poorly adapted. The panda coped with this by achieving exceptionally low energy expenditure through reducing the sizes of several vital organs and through maintaining a very low physical activity level and body temperature [13]. Thus, animals with low body temperatures may have undergone greater adaptations, or more adaptation events, than those with higher body temperatures.…”
Section: During Evolution Some Animals Emerged From and Later Returnmentioning
confidence: 99%
“…McNab [5] has measured the basal rate of the red panda and found that their basal rate was equal to 49% of the value expected from mass, which undoubtedly reflects its bamboo diet and possibly its arboreal habits. He estimated the basal rate of giant pandas according to the equation for 62 carnivorans that the expected basal rate is 59% of the value expected from body mass for a giant panda with body mass of 120 kg.Recently in a collaboration between scientists from the Institute of Zoology and the Institute of Genetics and Developmental Biology of the Chinese Academy of Sciences, and Beijing Zoo, new findings and advances on the energetics and physiology of giant pandas were published in Science [6]. They applied the doubly-labelled water method to measure the daily energy expenditure (DEE) of five captive pandas and three wild pandas.…”
mentioning
confidence: 99%
“…Recently in a collaboration between scientists from the Institute of Zoology and the Institute of Genetics and Developmental Biology of the Chinese Academy of Sciences, and Beijing Zoo, new findings and advances on the energetics and physiology of giant pandas were published in Science [6]. They applied the doubly-labelled water method to measure the daily energy expenditure (DEE) of five captive pandas and three wild pandas.…”
mentioning
confidence: 99%